Curriculum development in language teaching - Richards, Jack C. 1943- (Cambridge Univ. Press, 2001)
This text provides a systematic introduction to the issues involved in developing, managing, and evaluating effective second materials.
Hier auch später erschienene, unveränderte Nachdrucke. - Teilw. Verl. Ernst Klett aufgeklebt
Keywords: Sprache; Language and languages -- Study and teaching; Curriculum planning; Sprachunterricht; Curriculumentwicklung